Putting Health 4.0 at the service of Society 5.0: Exploratory insights from a pilot study. (March 2022) - Ciasullo, Maria Vincenza; Orciuoli, Francesco; Douglas, Alexander; Palumbo, Rocco
Abstract: The Health 4.0 paradigm is reshaping the attributes of health services' delivery. Alongside triggering institutional, structural, and cultural changes for health care organizations, it aims at achieving an increased patients and caregivers' participation in the value creation process. This is consistent with the transition towards Society 5.0 in health care. Drawing on the outcome of the research project "Health management system for managing bedsores in the home care setting", which was financed by the Operative Regional Programme of Campania, Southern Italy (Regional decree no. 614 dated October 29th, 2018 - CUP: B53D18000120007 - POR FESR Campania 2014/2020, O.S. 1.1), this study advances a Health 4.0 solution embedded in a mobile clinical Decision Support System intended to merge the diverging purposes of increasing health services' efficiency and boosting the quality of care by enacting value co-creation. The solution has been tested in a delicate health care setting, i.e. bedsores' treatment for home-care patients. The results of the pilot test suggest that Health 4.0 generates a twofold gain. On the one hand, it enables a more effective and timelier delivery of health services, curbing health exacerbations and tackling access to emergency care. On the other hand, it creates a digital-based empowering environment for patients and informal caregivers, activating them to perform as value co-creators. Health 4.0 should enter the socio-economic planning discourse in health care, being conceived of as a solution to enhance the economic viability and the social sustainability of health care systems. Highlights: Health 4.0 fosters the transition towards patient-centeredness. Health 4.0 solutions should be embedded in broader socio-economic planning interventions aimed at patient empowerment. Value co-creation and service co-production may be enabled by health 4.0 Health 4.0 may merge the diverging aims of curbing health care costs and increasing health services' quality. Health 4.0 enables a thick networking involving health professionals, patients, field operators, and caregivers.